MENINGKATKAN KINERJA PEMERINTAHAN DENGAN PEMANFAATAN TEKNOLOGI DIGITAL MELALUI TINJAUAN TATA KELOLA DI KABUPATEN JEMBER - Novelina, Mutiara (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2025)
This research aims to explore the relationship between digitalization and the governance of public administration in Jember. The study focuses on how technological advancements have influenced the efficiency, transparency, and accountability of government operations. Using a qualitative data analysis approach, the research examines various case studies, policy documents, and expert opinions to understand the implementation of digital systems in public administration. The study finds that digitalization has significantly improved the accessibility and delivery of public services, but challenges such as infrastructure limitations, digital literacy, and data privacy concerns remain. Moreover, the research highlights the need for a comprehensive digital governance strategy to ensure sustainability and inclusivity. The implications of these findings suggest that further investments in technology and human resource development are essential to achieving an effective and transparent public administration system. By addressing the identified challenges, digitalization can foster a more responsive and accountable government, benefiting the overall functioning of the state and the well-being of its citizens.